Socio-spatial perspectives on open-plan versus cellular offices. Issue 4 (24th July 2020) - Sailer, Kerstin; Thomas, Matt
Abstract : Purpose: This research provides a new perspective on the long-standing debate of open-plan versus cellular offices. It analyzes the effects of workplace layouts on organizational outputs such as innovation, efficiency and privacy by considering the physical space of an organization alongside its organizational structure. This socio-spatial approach draws on correspondence theory originating from space syntax to understand the potential for unplanned encounters between diverse groups of people. Design/methodology/approach: Three different organizations are studied, two open-plan and one cellular office. Floor and seating plans are analyzed to calculate the degree of correspondence between the spatial and conceptual closeness of people. Demands for each organization are derived from semi-structured interviews and publicly available information. Findings: The three studied organizations present very different degrees of openness toward others in ways that challenge conventional views of cellular and open-plan offices. In each case, the degree of correspondence matches the demands placed on the organization, and hence, providing a relatively good fit between the organization and interior environment. Research limitations/implications: A larger sample of open-plan and cellular offices would be useful to consider in further research. Practical implications: Managers can use the concept of correspondence to generate the appropriate degree of unplanned encounters between the right sets of people in order to achieve the best organization-environment fit. Originality/value: The main innovation of this paper lies in its socio-spatial approach, considering physical space alongside managerial, organizational choices.